Paradiplomation of The Island Cluster as an Effort to Increase Exports of Maluku Nutmeg - Dyah Ridhul Airin Daties; Efie Baadila (Faculty of Law, Universitas Pattimura, 2021)
Nutmeg is a spice plant native of the Maluku islands that have been traded and cultivated for generations in the form of smallholder plantations in most of the Maluku islands. However, currently, Maluku's nutmeg exports have decreased. Therefore, the Maluku government must be perspicaciously smart to read every opportunity so that the potential of natural resources can be utilized optimally for the welfare of the region. This research is normative juridical research, with the type of library research. Maluku Province is a province characterized by islands. This phenomenon is the background for the birth of the concept of island cluster development. Through the concept of island cluster development, the Maluku provincial government hopes that each island group realizes the potential of their respective regions and strives to develop this potential for the independence of each island group, especially in increasing Maluku nutmeg exports.